2018
DOI: 10.1038/s41427-018-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of current-induced effective magnetic field through Rashba effect engineering in hybrid multiferroic structures

Abstract: Current-induced effective magnetic fields offer a new pathway through spin orbit interaction (SOI) to switch magnetization and have recently attracted great interest. In the conventional heavy metal/ferromagnetic metal/oxide (HM/FM/Oxide) structure, significant efforts have been made to study the role of the HM in determining effective magnetic fields. However, very little attention has been paid to the oxide layer and its interface with FM, where the Rashba effect may affect the effective field. In this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…On the other hand, in the BFO films with different polarization fields, the migration of oxygen vacancies may affect the oxidation level of the thin films neighboring to BFO . If we deposit a FM/HM structure on a BFO film, the different polarization fields of BFO should affect SOT through the indirect control of the oxidation level in the FM layer, which is completely different from previous studies on PMN‐PT, ionic liquid gate, and BTO …”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…On the other hand, in the BFO films with different polarization fields, the migration of oxygen vacancies may affect the oxidation level of the thin films neighboring to BFO . If we deposit a FM/HM structure on a BFO film, the different polarization fields of BFO should affect SOT through the indirect control of the oxidation level in the FM layer, which is completely different from previous studies on PMN‐PT, ionic liquid gate, and BTO …”
Section: Introductionmentioning
confidence: 57%
“…Yang et al reported the electric‐field control of SOTs in a Pt/Co/GdO x heterostructure through oxygen ions migration . And Chen et al had used a ferroelectric oxide of BaTiO 3 to tune the field‐like effective field by engineering the Rashba effect, which can only be observed at low temperatures (≈10 K). However, how to realize effective and stable control of SOT by multiferroic materials and their polarization fields above room temperature remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the quantified current‐induced spin–orbit field refers to the damping‐like effective field that is the driving force for the magnetization switching. [ 18 ] Figure 2d shows the AHE loops at ±1.5 mA under a bias IP magnetic field of 8.5 kOe. It can be seen that the AHE loops shift toward opposite directions under opposite DC, indicating the existence of a current‐induced effective field due to the SOT.…”
Section: Resultsmentioning
confidence: 99%
“…However, further enhancement of controlling SHE and even the sign by applying an external voltage bias is limited by the magnitude of the electric field itself. On the other side, ferroelectric materials that can generate strong electric fields through spontaneous polarization hold promise for offering nonvolatile control of various spintronic devices. …”
mentioning
confidence: 99%